PENGARUH PAD, DAU, DAK, DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI ACEH - melva nava (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
This study aims to identify and analyze the effect of LR, GAF, SAF, and Capital Expenditures on Economic Growth in Aceh regencies/cities. The population used in this study were 18 districts and five cities in Aceh regencies/cities from 2015-2019 using saturated sampling techniques. The data used in this study is secondary data taken directly from the Aceh Central Statistics Agency, namely the realization of the Anggaran Pendapatan serta Belanja Kabupaten (APBD). The research method used is multiple linear regression. The results of partial research show that LR has a positive and significant effect on Economic Growth, but GAF, SAF, and Capital Expenditures do not affect economic growth in Aceh regencies or cities. Meanwhile, simultaneously displaying LR, GAF, SAF, and Capital Expenditures significantly affect Economic Growth in Aceh regencies or cities